Studying the Photocatalytic Degradation of Tri-n-Butyl Phosphate Using Nano Nd-Doped TiO2 - H. Ghasemi Mobtaker; A. Malekinejad; T. Yousefi; H. Aghayan (Journal of Sciences, Islamic Republic of Iran)
Photocatalytic method was used as an efficient and simple way for degradation of tri-n-butyl phosphate (TBP). In contrast to other methods, in this method the mineralization occurs and no twin pollution is generated. Nd doped TiO2 was synthesized via sol gel process and characterized by XRD and TEM tecniuqes. Then it was used as photocatalyst for TBP degradetion. It was found that the solution pH has important effect on degradation efficiency and kinetic. Degradation was more efficient in both acidic and alkali media. The kinetic studies indicated that the second order model at neutral pHs range was the dominant while in acidic or alkali conditions the kinetic models were first and third order respectively. By proceeding the degradation process, some products and byproducts are generated, which lead to the change of the solution pH and change of degradetion mechanism and kinetic. The LC MS was used to detect the intermediate and final products. Results showed that the method has high efficiency and is a promising procedure for decomposition of TBP.